Jharkhand Draft Annual Plan 2002-2003 and Xth Five Year Plan 2002-2007 - Planning Commission (Planning Commission, 2002)
The newly created Jharkhand State which has an area of 79714 sq, km. has the potential to develop as the most financially viable state in the whole country because of its mineral based resources and the industrial infrastructure available in the state. But still the basic of the economy is agriculture and allied activities. The State of Jharkhand has a total geographical area of 79.7 lakh ha. out of which cultivable land is 38 lakh ha. and the present net sown area is 18.04 lakh ha. The net irrigated area is only 1.57 lakh ha. which is 8% of the net sown area. More than 29% land is covered as forest areas and 25% of land is covered as sown areas.
Planning Development and Programme Implementation Department Government of Jharkhand